ИНГЛИС ҲӘМ ҚАРАҚАЛПАҚ ТИЛЛЕРИНДЕГИ САЛТ-ДӘСТҮРЛЕР ҲӘМ ИСЕНИМ (ЫРЫМ) ЛЕКСИКАСЫНЫҢ ЭТНОЛИНГВИСТИКАЛЫҚ АНАЛИЗИ - Арзиева, Б.А. (ILIM hám JÁMIYET, 2023)
This article deals with the ethno linguistic analysis of the English and Karakalpak traditions, the meaning of the word of Belief, the concept of ethno linguistics, the origin of ethno cultural information, the lexico-semantic analysis of the lexeme Belief, and the analysis of the meanings of the lexeme of Belief in English dictionaries.